Equity Issue and a Long-Term Effect of Equity Market Timing on Capital Structure - Miswanto, Miswanto; ., . (International Journal of Engineering and Technology, 2018)
After the research about a short term effect of equity market timing on capital structure, the author is motivated to do research about a long term effect of equity market timing on capital structure of the firms which is listed in Indonesia Stock Exchange. The main problems on this research are to understand whether firms use equity market timing theory when issuing equity, and whether equity market timing has a long term effect on its capital structure. Then the purpose of this study is to examine the problems of this research. There are two hypothesis in this research. First, firms use equity market timing when issuing equity, and second, equity market timing has a long term effect on capital structure of firms in Indonesia. This research uses non-financial companies listed on the Indonesia Stock Exchange over the period of 2001 to 2011 as the sample. The data used in this research are panel data. The sample choosing is based on sample non-probability sampling using purposive sampling in form of judgment sampling. The research model used in this study is a distributed-lag regression model. The results of this research show that firms use equity market timing when issuing equity, and equity market timing does not have a long term effect on capital structure of firms in Indonesia. Thus, because there is deviation on the capital structure, then there is an indication that the firms will perform the process of speed adjustment towards the targeted capital structure, the optimum capital structure.Â